Measuring science: is there "basic research" without statistics? - Godin, Benoit (2003)
Basic research is a central concept of science and science policy. This article examines the role statistics played in helping to create the concept and shows how it was in part constructed by statistics to serve social and political agendas. Most of this statistical work was conducted in the United States in the 1940s and 1950s, then standardized by the OECD in the 1960s. - Reproduced.
Keywords: Fundamental research